2019
DOI: 10.1038/s41598-019-47014-w
|View full text |Cite
|
Sign up to set email alerts
|

Cimp-Positive Status is More Representative in Multiple Colorectal Cancers than in Unique Primary Colorectal Cancers

Abstract: Colorectal cancer (CRC) with CpG island methylator phenotype (CIMP) is recognized as a subgroup of CRC that shows association with particular genetic defects and patient outcomes. We analyzed CIMP status of 229 individuals with CRC using an eight-marker panel ( CACNA1G , CDKN2A , CRABP1 , IGF2 , MLH1 , NEUROG1 , RUNX3 and SOCS1 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
3
11
2
Order By: Relevance
“…In this sense, also the large rate of CIMP-High tumors within this population (75%) might confirm the contribution of epigenetic alterations to field effects previously proposed 29 , 31 . These findings are also in accordance with our previous studies in which we concluded that CIMP+ tumors were more frequent in patients diagnosed with SCRC than in patients with an isolated CRC or MCRC 20 , 21 . Interestingly, we observed some molecular alterations that appeared to be linked with the SRC subset.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this sense, also the large rate of CIMP-High tumors within this population (75%) might confirm the contribution of epigenetic alterations to field effects previously proposed 29 , 31 . These findings are also in accordance with our previous studies in which we concluded that CIMP+ tumors were more frequent in patients diagnosed with SCRC than in patients with an isolated CRC or MCRC 20 , 21 . Interestingly, we observed some molecular alterations that appeared to be linked with the SRC subset.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have demonstrated molecular concordance between tumors within the same individual although definitive results have not yet been achieved 15 19 . Indeed, our group recently published the possible clonal origin of a subset of SCRCs diagnosed in patients without hereditary forms of CRC 20 , and highlighting the significance of epigenomic patterns in the development of multiple primary neoplasms 21 . Because pathogenesis and clinical features largely depend on the location of the tumor in the colonic mucosa, a correlation between the hypothetical molecular basis of SCRC and the anatomical location in the colon has been proposed 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Other current studies apply IGF2 in a panel with other CRC-specific markers (e.g., CACNA1G , CDKN2A , CRABP1 , IGF2, MLH1 , NEUROG1 , RUNX3 , and SOCS1 ) to study the CpG island methylator phenotype (CIMP) phenotype in primary and metastatic CRC [25,70,160]. Recent study showed higher CIMP(+) frequency in patients diagnosed with multiple CRC than in patients with “unique” CRC [161]. It was proven that CIMP-high cancers had poor survival outcomes in CRC patients [160].…”
Section: Known and Less Known Alterations Of Igf2 In Colorectal Camentioning
confidence: 99%
“…Aneuploidy can be a result of many factors, including chromosome segmentation defects at the mitotic checkpoint and inactivating mutations in DNA damage repair genes [13]. The heterogeneous nature of CRCs origin, specifically within terms of its genetic instability, provides both a challenge in diagnosis and an opportunity for risk stratification [14]. Genetic instability can occur in three different forms in CRC: CpG island methylation phenotype, microsatellite instability (MSI) resulting from defective repair of mismatched bases and chromosomal instability (CIN) leading to aneuploidy [15].…”
mentioning
confidence: 99%
“…CpG island methylation phenotype is associated with the silencing of tumor suppressor and DNA repair genes. It is associated with the right colon, mucinous features, MSI, poor tumor differentiation, high BRAF mutation rates and the female population [14]. MSI tends to arise in the right colon, is associated with a slightly better prognosis and responds differently to chemotherapy; thus, its treatment is specialized [16].…”
mentioning
confidence: 99%